Multiple Sclerosis and Cancer: The Ying-Yang Effect of Disease Modifying Therapies - Melamed, Esther; Lee, Michael William (Frontiers in Immunology, 2020)
Over the past two decades, the field of multiple sclerosis (MS) has been transformed by the rapidly expanding arsenal of new disease modifying therapies (DMTs). Current DMTs for MS aim to modulate innate and adaptive immune responses toward a less inflammatory phenotype. Since the immune system is also critical for identifying and eliminating malignant cells, immunosuppression from DMTs may predictably increase the risk of cancer development in MS patients. Compared with healthy controls, patients with autoimmune conditions, such as MS, may already have a higher risk of developing certain malignancies and this risk may further be magnified by DMT treatments. For those patients who develop both MS and cancer, these comorbid presentations create a challenge for clinicians on how to therapeutically address management of cancer in the context of MS autoimmunity. As there are currently no accepted guidelines for managing MS patients with prior history of or newly developed malignancy, we undertook this review to evaluate the molecular mechanisms of current DMTs and their potential for instigating and treating cancer in patients living with MS.